METHODS OF MINIMALLY INVASIVE DECOMPRESSION OF THE BILIARY TRACT WITH MECHANICAL JAUNDICE - K. M. Kurbonov; K. R. Nazirboev (Вестник хирургии имени И.И. Грекова)
OBJECTIVE. The aim of the study is to improve the results of treatment of patients with mechanical jaundice. MATERIAL AND METHODS. The results of treatment of 350 patients with mechanical jaundice of benign genesis were analyzed. The causes of this disease in 230 (68.6 %) cases were choledocholithiasis, in 75 (21.4 %) cases were cicatrical narrowing of the large papilla of the duodenum (n = 50), in 45 cases were the formed biliodigestive anastomoses (n=25) and chronic pancreatitis (12.8 %). RESULTS. To eliminate mechanical jaundice, 154 (44 %) patients underwent various percutaneous decompressive echo-controlled interventions under the ultrasound control in terms of their nature and volume. In addition, endoscopic transpapillary interventions were performed in 196 (56 %) observations. various postoperative complications were noted after performing percutaneous decompressive echo-control interventions under ultrasound in 14 (4 %) observations, and after endoscopic transpapillary interventions in 21 (6 %) cases. CONCLUSION. Minimally invasive endoscopic and echo-controlled interventions as the first stage of surgical treatment are effective methods of treatment of patients with mechanical jaundice.